Edukasi Pembuatan Keripik Jambu Kristal dengan Vacuum Frying bagi Petani Buah di Rasau Jaya Kubu Raya Kalimantan Barat - Dwi Gusmalawati; Oke Anandika Lestari; Surya Abi Alfariz (I-Com: Indonesian Community Journal, 2024)
Crystal guava is an agricultural fruit for the community in Rasau Jaya Village, Kubu Raya, West Kalimantan. Crystal guava is marketed in the form of fresh fruit with a relatively high and stable price. However, when the fruit harvest is abundant, guavas that are not immediately processed/consumed are easily rotten, causing farmers to lose money. Making fruit chips is a post-harvest processing effort that can increase selling value and overcome fruit damage. The purpose of this activity was to educate fruit farmers in Rasau Jaya through making crystal guava chips for post-harvest fruit management and increasing selling value to overcome losses. Partners in this activity were fruit farmers in Rasau Jaya. The method in this activity was training (theory delivery, demonstration and practice). Education participants were satisfied with the activity of making crystal guava chips (90%) and gained additional knowledge and skills (95%). Participants hope that after participating in this activity they can process crystal guava into chips so as to increase income and minimise losses due to guava damage.